Asymptotics of a solution of a discontinuous singularly perturbed Cauchy problem - Mel'nik, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We construct the asymptotic expansion of a solution of the Cauchy problem for a singularly perturbed system of differential equations whose right-hand side is discontinuous on a certain surface. We consider the case where the surface of discontinuity is crossed and estimate the remainder of the constructed asymptotic expansion.